1989
DOI: 10.1111/j.1349-7006.1989.tb02336.x
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Expression of E‐Cadherin Adhesion Molecules in Metastatic Ovarian Tumor Cells

Abstract: E‐Cadherin is a member of the cadherin family, which plays a key role in intercellular adhesion in various tumors as well as in normal tissues. Here, we examined the expression of this adhesion molecule in a murine ovarian tumor line OV2944, whose sublines show different degrees of spontaneous metastasis from subcutaneous sites; sublines LM‐1 and LM‐3 exhibit a low metastatic activity but a variant subline HM‐1 has a high metastatic activity. When the expression of E‐cadherin in these cells was examined by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 14 publications
5
65
0
2
Order By: Relevance
“…One is that the cytoplasmic reactivity indicates a reversible change in Ecadherin expression by the cell in response to the local environment. It has been demonstrated that E-cadherin expression can easily be altered in vitro in response to the culture environment and that highly metastatic ovarian tumour cells have unstable E-cadherin expression (Hashimoto et al, 1989). Such a temporal disruption of E-cadherin-mediated adhesion would allow tumour cell detachment, while re-expression could favour colonisation at a distant site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is that the cytoplasmic reactivity indicates a reversible change in Ecadherin expression by the cell in response to the local environment. It has been demonstrated that E-cadherin expression can easily be altered in vitro in response to the culture environment and that highly metastatic ovarian tumour cells have unstable E-cadherin expression (Hashimoto et al, 1989). Such a temporal disruption of E-cadherin-mediated adhesion would allow tumour cell detachment, while re-expression could favour colonisation at a distant site.…”
Section: Discussionmentioning
confidence: 99%
“…A more complex relationship has been observed between unstable or aberrant expression of cadherins and metastatic potential of tumour cells (Hashimoto et al, 1989;Mareel et al, 1991). While a clear role for E-cadherin in preventing tumour cell invasion has emerged from these in vitro studies, the relationship between E-cadherin expression in primary tumours and other prognostic parameters is inconsistent.…”
mentioning
confidence: 95%
“…In contrast to the other cell-cell adhesive receptors, dysfunction in the regulation of cadherin expression might very well be involved in cancer development and progression (Takeichi, 1991;Umbas et al, 1992). Furthermore, E-cadherin is well known to be an invasive suppressor in tumour progressions, because expression levels for E-cadherins were reduced in almost all the malignant tumours and not correlated with their metastatic abilities (Behrens et al, 1989;Hashimoto et al, 1989). Additionally, a recent report suggested the possibility that some carcinoma cells lose E-cadherin expression during the process of detaching from the primary sites and infiltrating other sites (Matsuura et al, 1992); another elucidated that some Ecadherin functions expressed on the cancerous cell surfaces are impaired by loss or down-regulation of cytoplasmic proteins designated 'catenins' (Shimoyama et al, 1992).…”
Section: Subjectsmentioning
confidence: 99%
“…E-cadherin, also termed uvomorulin or Cell-CAM120/80, is a cell-adhesive molecule found in epithelial cells in a variety of embryonic and adult tissues (Damsky et al, 1983;Ogou et al, 1983;Vestweber & Kemler, 1984). Several recent studies suggested that loss of E-cadherin may be associated with tumour progression in epidermal carcinogenesis as well (Navarro et al, 1991), and E-cadherin acts particularly as a suppressor of invasive ability (Behrens et al, 1989;Chen & Obrink, 1991;Frixen et al, 1991;Mareel et al, 1991;Vleminckx et al, 1991) or metastatic phenotype (Hashimoto et al, 1989;Schipper et al, 1991). In adult organisms, each cadherin displays a characteristic tissue distribution pattern, although expression is not tissue specific (Takeichi, 1991).…”
mentioning
confidence: 99%
“…HM-3 is a sub line of OV2944 which is a ovarian tumor cell line of B6C3F1 origin [31]. IG10 is a mouse ovarian cancer cell line of C57BL/6 origin [32].…”
Section: Introductionmentioning
confidence: 99%